Using targeted therapies at the end of life. Issue 3 (27th August 2020) - Delaye, Matthieu; Scotte, Florian; Voisin-Saltiel, Sabine; Pavliuc, Elena; Vigouret-Viant, Laurence; Dauchy, Sarah; Mateus, Christine
Abstract : The prescription of chemotherapy during the last weeks of a patient's life is a recognised criterion of decreasing quality of life but also survival. Targeted therapies have a particular efficiency and tolerance profile raising the question of their use in a palliative setting. Two patients were treated for a melanoma, at terminal stage, with poor efficiency of the symptomatic treatments. We introduced targeted therapies, which was previous treatments used in both patients.The evolution and benefits of the treatment was very different in our two patients and make us discuss the interest of targeted therapies in an end-of-life context and propose criteria for their maintenance or introduction in this indication. This discussion requires close collaboration between oncologists and palliative physicians and a very clear information given to patients and their relatives.